The AI Revolution in Health Education: Personalized Learning and Enhanced Health Literacy - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into healthcare is rapidly moving from a theoretical concept to a practical reality. While much of the discussi...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Medical Ethics